6ER-023 Establishment of group work: what is the effect on the state of knowledge and perception of pharmacovigilance among our future moroccan pharmacists?. (March 2019) - Nchinech, N; Lachhab, Z; Cherrah, Y; Serragui, S
Abstract : Background: For pharmacy students, the time devoted to the 'adverse effects and pharmacovigilance' module was 2 hours in the first year. A first assessment of knowledge showed a low level of knowledge concerning adverse effects and pharmacovigilance, following which tutorials have been added to the training programme. Purpose: To evaluate the state of progress of knowledge and perception of students in the second year of pharmacy education with regard to adverse drug reaction (ADR) and pharmacovigilance, after the introduction of a work groups system. Material and methods: This was a monocentric descriptive study conducted in the pharmacology laboratory of the Faculty of Medicine and Pharmacy of Mohammed V University of Rabat, for all students of the second year of pharmacy for the academic year 2017–2018, by means of a questionnaire of the knowledge and perception of pharmacovigilance distributed in the middle of the second semester, from 16 to 19 April 2018 at the end of the sessions of interactive work groups concentrating, for the first time, on pharmacovigilance. Results: Of the 122 students in the class, the response rate was 95.90% (n=117). The work group helped to better explain to the students the reporting circuit, however 28 participants reported their inability to report ADR in their future practice (25.92%). Regarding the obligation to report ADRs, 99.4% of students (n=116) thought that it should be made legally valid for all health professionals. The same number (n=116) found the role of pharmacovigilance to be important. In addition, almost all of the comments collected after the tutorials reflected students' appreciation of this initiative and their desire to receive more sessions. Conclusion: In this study, students expressed the desire to learn more about pharmacovigilance during their university education. This result led to the introduction of a system of pharmacovigilance work groups for third- and fourth-year pharmacy students for the 2018–2019 academic year. References and/or acknowledgements: Thanks to all participants. No conflict of interest.